2008
DOI: 10.2478/s11686-008-0009-8
|View full text |Cite
|
Sign up to set email alerts
|

Histological investigations of Eimeria infection in large-scaled gurnards, Lepidotrigla cavillone (Lacepède, 1801) from the Novigrad Sea, Croatia

Abstract: The presence of an Eimeria sp. was found in adult large-scaled gurnards Lepidotrigla cavillone (LacepPde, 1801) from the Novigrad Sea, in Croatia. The detection of Eimeria sp. in the pyloric caeca and intestines of the large-scaled gurnards is also the first report of the parasite in this fish species. The analysis of histopathological changes in the digestive tract led to the conclusion that the parasite could be a serious pathogen in heavily infected large-scaled gurnards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…While it does not supply all the answers, the high prevalence of the Eimeria infection in association with severe pathology showed that it is a significant disease under nursery culture conditions in Ca Mau, one which will need to be managed. Significant pathology was frequently reported in fish with apicomplexan infections (Benajiba et al 1994;Molnar 2006;Gjurcevic et al, 2008;Morrison et al, 1993;Jendrysek et al, 1994;Hemmer et al, 1998). Although systemic iridoviral disease was also observed, it was not as consistently observed as the Eimeria infection in diseased fish.…”
Section: Discussionmentioning
confidence: 99%
“…While it does not supply all the answers, the high prevalence of the Eimeria infection in association with severe pathology showed that it is a significant disease under nursery culture conditions in Ca Mau, one which will need to be managed. Significant pathology was frequently reported in fish with apicomplexan infections (Benajiba et al 1994;Molnar 2006;Gjurcevic et al, 2008;Morrison et al, 1993;Jendrysek et al, 1994;Hemmer et al, 1998). Although systemic iridoviral disease was also observed, it was not as consistently observed as the Eimeria infection in diseased fish.…”
Section: Discussionmentioning
confidence: 99%
“…Since existing reports of the ultrastructure of this parasite are lim-*Corresponding author: stanball@ongar.fsnet.co.uk Ultrastructure of Goussia metchnikovi 21 ited (Lom and Dyková 1992), we have investigated by transmission electron microscopy (TEM), the gamogonic stages, with some observations on the sporulated oocysts, sporocysts and the host tissue reaction, especially since the histopathology of coccidian infections in fishes is little understood (Gjurčević et al 2008). …”
Section: Introductionmentioning
confidence: 99%